2020
DOI: 10.1111/pbi.13393
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TaIRX9b gene function in wheat decreases chain length and amount of arabinoxylan in grain but increases cross‐linking

Abstract: Wheat contains abundant xylan in cell walls of all tissues, but in endosperm, there is an unusual form of xylan substituted only by arabinose (arabinoxylan; AX) that has long chains and low levels of feruloylation, a fraction of which is extractable in water (WE-AX). WE-AX acts as soluble dietary fibre but also gives rise to viscous extracts from grain, a detrimental trait for some nonfood uses of wheat. Here, we show that a glycosyl transferase family 43 wheat gene abundantly expressed in endosperm complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…The proportions of short AXOS released by GH11 digestion were decreased more in the single GT43_1 and triple lines (to 33%, 35%) lines than total AX, as was the proportion of WE-X (decreased to 21%, 20%) ( Table 2 ). This was also the case in our previous studies of RNAi suppression of GT43_2 and GT47_2 and of a triple mutant of GT43_2, where suppression of these genes induced a change in AX composition such that the solubility and digestibility with the GH11 endoxylanase were decreased [ 10 , 15 , 28 ]. This could be because suppression of these genes knock-outs xylan synthase complexes which synthesis a specific type of AX, or because the loss of cell AX in the endosperm cell walls results in compensatory increases in AX cross-linking: there was evidence of such compensation in our previous studies [ 15 , 29 ] but that does not rule out the first hypothesis.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The proportions of short AXOS released by GH11 digestion were decreased more in the single GT43_1 and triple lines (to 33%, 35%) lines than total AX, as was the proportion of WE-X (decreased to 21%, 20%) ( Table 2 ). This was also the case in our previous studies of RNAi suppression of GT43_2 and GT47_2 and of a triple mutant of GT43_2, where suppression of these genes induced a change in AX composition such that the solubility and digestibility with the GH11 endoxylanase were decreased [ 10 , 15 , 28 ]. This could be because suppression of these genes knock-outs xylan synthase complexes which synthesis a specific type of AX, or because the loss of cell AX in the endosperm cell walls results in compensatory increases in AX cross-linking: there was evidence of such compensation in our previous studies [ 15 , 29 ] but that does not rule out the first hypothesis.…”
Section: Discussionsupporting
confidence: 66%
“…RNAi down-regulation of the single xylan synthase subunit encoded by GT43_1 and simultaneous down-regulation of all three subunits (encoded by GT43_1, GT43_2, GT47_2) resulted in similar decreases in total AX, to 46% and 47% of the total X determined by monosaccharide analysis ( Table 2 ). This compares with previously reported RNAi down-regulation of single xylan synthase subunit genes (GT43_2 or GT47_2) which resulted in decreases in total AX [ 10 ] to 50–60% of those in the control lines and the development of a triple knock-out mutant of GT43_2 (stacking mutations in A,B,D homeologues of GT43_2A,B,D/TaIRX9b) in which total AX was reduced to about 65% of that in the control line [ 15 ]. The proportions of short AXOS released by GH11 digestion were decreased more in the single GT43_1 and triple lines (to 33%, 35%) lines than total AX, as was the proportion of WE-X (decreased to 21%, 20%) ( Table 2 ).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…The xax1 rice mutants which had reduced xylan and a lower degree of diferulate cross-links, also exhibited ~10% increase in terminal arabinose [ 54 ]. More recently Pellnny et al (2020) [ 55 ] have shown that knocking down expression of three Ta IRX9B (orthologs of Arabidopsis irx9) genes in wheat endosperm resulted in reduced levels of AX and increased ferulate dimerization. These observations, which are in line with the data presented here, points to a compensatory mechanism in plants that indicates a level of interdependence between different groups of cell wall components.…”
Section: Discussionmentioning
confidence: 99%